PHYSICO-GEOLOGICAL MODEL OF THE PROJECTING HYDROTECHNICAL OBJECT AS A BASIS OF SELECTION OF THE COMPLEX OF GEOPHYSICAL METHODS OF RESEARCHES (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The problems of compiling the physico-geological model (PGM) of the investigated territory were considered for predetermining the possible complex of geophysical methods for solving tasks. Аs an example, the PGM of Meghri HPP (Armenia) projected hydrotechnical tunnel territory is considered.
Keywords: physico-geological model; geophysical modeling of complex; hydrotechnical tunnel; geological section; physical properties of rocks